Nonequilibrium quantum dynamics of partial symmetry breaking for ultracold bosons in an optical lattice ring trap - Zhao, Xinxin; Carr, Lincoln D. (New journal of physics, 2019)
A vortex in a Bose-Einstein condensate on a ring undergoes quantum dynamics in response to a quantum quench in terms of partial symmetry breaking from a uniform lattice to a biperiodic one. Neither the current, a macroscopic measure, nor fidelity, a microscopic measure, exhibit critical behavior. Instead, the symmetry memory succeeds in identifying the critical symmetry breaking at which the system begins to forget its initial symmetry state. We further identify a symmetry energy difference in the low lying excited states which trends with the symmetry memory.
Gesehen am 18.07.2019